Digital Banking Program to Improve Performance in Sharia Banking in Indonesia - Asep Ghofir Ali (AIBPM Publisher, 2025)
The share of Sharia banking in Indonesia remains relatively low compared to its conventional counterparts, primarily due to challenges such as limited product innovation, expensive third-party funds, and inadequate digital infrastructure. As digital transformation becomes a necessity in the financial sector, this study aims to analyze the influence of digital banking programs on the performance of Sharia banking in Indonesia. The research adopts a descriptive and verification method using a census approach involving 27 Sharia banks across the country. Data were collected through a structured questionnaire and analyzed using Partial Least Squares (PLS). The results indicate a significant positive impact of digital banking implementation on Sharia banks' business performance, measured through financial and non-financial indicators. These findings suggest that effective digital strategies aligned with Sharia principles can enhance competitive advantage and institutional performance. This study contributes to the growing literature on Islamic digital finance and provides practical implications for decision-makers in optimizing digital transformation initiatives in the Sharia banking sector.